Gonadal dysgenesis: A case report - Rocca G., Ennio (2015)
A woman 17 years old with primary amenorrhea and shortness stature is presented, the parient had adequate development of the breast and pubic hair, however the chromatin sex was of the mole type and the uterus was absent; urinary gonadotrophins were high. The authors comment the different forms that gonadal dysgenesis can present.